Eksistensi Parmalim Mempertahankan Adat dan Budaya Batak Toba di Era Modern - Dapot Siregar; Yurulina Gulo (Universitas Negeri Medan, 2020)
This paper aims to describe and critically analyze the existence of Parmalim in an effort to maintain Toba Batak customs and culture in the modern era. The problem is focused on the rites of worship and social life of Parmalim in Laguboti and Hutatinggi. The extent to which the Malim religion uses the customs and culture of the Toba Batak in every rite and social life every day as an effort to maintain the customs and culture of the Toba Batak in the modern era. To approach this problem, researchers depart from the reference to the theory of modernity, where in modernity emphasizes rational, which is irrational will be abandoned. In addition, researchers will also approach through the theory of the function of religion, in which in the theory of the function of religion that religion still functions if it is able to provide explanation, spiritual comfort and to bind existing social cohesion. The research method was conducted by the writer through in-depth interviews with several community leaders covering the regions of Laguboti and Hutatinggi and also literature studies.